Worldview Islam sebagai Framework Filsafat Islam Hakikat, Idealisme dan Realitas - Kardiyanto, Wawan (IAIN Surakarta, 2018)
This article aims to explain the worldview of Islam as a framework of Islamic philosophy of essence, idealism and reality by using comparative methodology between Islam and the West (orientalist). According to the theory of the worldview Alparslan, the inability to absorb sophisticated Greek thought (sophisticated reading) is due to the poor mechanism to produce a scientific conceptual scheme in the view of life. Peters facts that Christians can not complete the translation of Organon are understood in the perspective of the worldview of Islam. The concept of Western scholarship came after they came into contact with Muslim civilization. This process is recognized by other Western writers as